ATP‐P2Y2‐β‐catenin axis promotes cell invasion in breast cancer cells. Issue 7 (6th June 2017) - Zhang, Jiang‐Lan; Liu, Ying; Yang, Hui; Zhang, Hong‐Quan; Tian, Xin‐Xia; Fang, Wei‐Gang
Abstract : Extracellular adenosine 5′‐triphosphate (ATP), secreted by living cancer cells or released by necrotic tumor cells, plays an important role in tumor invasion and metastasis. Our previous study demonstrated that ATP treatment in vitro could promote invasion in human prostate cancer cells via P2Y2, a preferred receptor for ATP, by enhancing EMT process. However, the pro‐invasion mechanisms of ATP and P2Y2 are still poorly studied in breast cancer. In this study, we found that P2Y2 was highly expressed in breast cancer cells and associated with human breast cancer metastasis. ATP could promote the in vitro invasion of breast cancer cells and enhance the expression of β‐catenin as well as its downstream target genes CD44, c‐Myc and cyclin D1, while P2Y2 knockdown attenuated above ATP‐driven events in vitro and in vivo . Furthermore, iCRT14, a β‐catenin/TCF complex inhibitor, could also suppress ATP‐driven migration and invasion in vitro . These results suggest that ATP promoted breast cancer cell invasion via P2Y2‐β‐catenin axis. Thus blockade of the ATP‐P2Y2‐β‐catenin axis could suppress the invasive and metastatic potential of breast cancer cells and may serve as potential targets for therapeutic interventions of breast cancer. Abstract : In this study, we demonstrated for the first time that ATP‐P2Y2‐β catenin axis promoted breast cancer cell invasion. Blocking P2Y2‐β‐catenin axis could suppress the metastatic potential of breast cancer cells and may serve as potential targets for therapeutic interventions of breast cancer.